PSYCHOANAL YTIC LITERARY CRITICISM OF AMERICAN ROMANTICISM LITERATURE AS REFLECTED IN NARRATIVE OF THE LIFE OF FREDERICK DOUGLASS - Didik Murwantono (Celt: A Journal of Culture, English Language Teaching & Literature, 2011)
One of the most prominent themes in the Narrative involves the association of literacy with freedom. Within the context of Afro-American literature, slave narratives have attracted a great deal attention in recent criticism due to the fact that they represent the origins of the desire to search for an appointment and represent vehicle to portray the reality of Black identity. In this paper, it merely focuses on the psychological aspects of Frederick Douglass to escape from slavery influenced by the romantic era. In this work, instead of telling his life in a set of events, Frederick Douglass wrote in aform of an autobiography in which he could put forward his feelings-regret, fear, sadness, hope and enthusiasm, love, and despair personally. It shows how instead of sinking him to a weak and helpless condition, Douglass's feelings make him strong and firm to determine his path to gain freedom. That is the characteristic of romantic feelings.